Evolutionary dynamics and molecular epidemiology of West Nile virus in New York State: 1999–2015. Issue 2 (21st July 2019) - Bialosuknia, Sean M; Tan, Yi; Zink, Steven D; Koetzner, Cheri A; Maffei, Joseph G; Halpin, Rebecca A; Mueller, Emmi A; Novotny, Mark; Shilts, Meghan; Fedorova, Nadia B; Amedeo, Paolo; Das, Suman R; et al.
Abstract: Following its introduction into New York State (NYS) in 1999, West Nile virus (WNV; Flavivirus, Flaviviridae ) underwent a rapid expansion throughout the USA and into Canada and Latin America. WNV has been characterized as being evolutionarily stable, with weak geographic structure, a dominance of purifying selection and limited adaptive change. We analyzed all available full-genome WNV sequences, focusing on the 543 available sequences from NYS, which included 495 newly sequenced 2000–15 isolates. In addition, we analyzed deep-sequencing data from 317 of these isolates. While our data are generally in agreement with the limited pace of evolutionary change and broad geographic and temporal mixing identified in other studies, we have identified some important exceptions. Most notably, there are 14 codons which demonstrated evidence of positive selection as determined by multiple models, including some positions with evidence of selection in NYS exclusively. Coincident with increased WNV activity, genotypes possessing one or more of these mutations, designated NY01, NY07, and NY10, have increased in prevalence in recent years and displaced historic strains. In addition, we have found a geographical bias with many of these mutations, which suggests selective pressures and adaptations could be regional. Lastly, our deep-sequencing data suggest both increased overall diversity in avian tissue isolates relative to mosquito isolates and multiple non-synonymous minority variants that are both host-specific and retained over time and space. Together, these data provide novel insight into the evolutionary pressures on WNV and the need for continued genetic surveillance and characterization of emergent strains.